Electronic Diplomacy from the Perspective of the Main Theories in International Relations - Al-Barzanji , Prof. Dr. Dana Ali Saleh; Aziz, Lecture. Aryan Raouf (The International and Political Journal, 2023)
This research deals with an important and recent topic that has not yet received proper theoretical attention, and here lies its importance which is electronic diplomacy in the perspective of the main theories of international relations, especially realism, liberalism, and constructivism, in order to inform researchers and decision-makers on how to address this new topic in these theories. The problem here lies in the question, to what extent are these theories interested in electronic diplomacy? How do we find theoretical approaches to it? By following the descriptive and comparative approach, the research attempted to branch out from the validity of its hypothesis, which says: Despite the fact that realism is not interested in electronic diplomacy, there are intellectual approaches in my liberal and constructivist theories to theorize the importance of electronic diplomacy and its role in global relations. The research reached a major conclusion that despite neglecting the realism of electronic diplomacy, my liberal and constructivist theories have intellectual approaches to explain the role of electronic diplomacy, which is based on a complex relationship between public diplomacy, soft power, and identity, and thus the research proved the validity of its hypothesis.